CRISPR-cas system in the acquisition of virulence genes in dental-root canal and hospital-acquired isolates of Enterococcus faecalis - Pourya Gholizadeh (Taylor & Francis Group, 2020)
Enterococcus faecalis is one of the important causative agents of nosocomial and life-threatening infections in human. Several studies have demonstrated that the presence of CRISPR-cas is associated with antibiotic susceptibility and lack of virulence traits. In this study, we aimed to assess the phenotypic and genotypic virulence determinants in relation to CRISPR elements from the dental-root canals and hospital-acquired isolates of E. faecalis. Eighty-eight hospital-acquired and 73 dental-root canal isolates of E. faecalis were assessed in this study. Phenotypic screening of the isolates included biofilm formation, and gelatinase and hemolysis activities. Genotypical screening using PCR was further used to evaluate the presence of CRISPR elements and different virulence-associated genes such as efaA, esp, cylA, hyl, gelE, ace, ebpR, and asa1. Biofilm formation, gelatinase, and hemolysis activities were detected in 93.8%, 29.2%, and 19.2% of the isolates, respectively. The most prevalent virulence-associated gene was ace, which was followed by efaA, whereas cylA was the least identified. The presence of CRISPR1-cas, orphan CRISPR2, and CRISPR3-cas was determined in 13%, 55.3%, and 17.4% of the isolates, respectively. CRISPR elements were significantly more prevalent in the dental-root canal isolates. An inverse significant correlation was found between CRISPR-cas loci, esp, and gelE, while direct correlations were observed in the case of cylA, hyl, gelE (among CRISPR-loci 1 and 3), asa1, ace, biofilm formation, and hemolysis activity. Findings, therefore, indicate that CRISPR-cas might prevent the acquisition of some respective pathogenicity factors in some isolates, though not all; so selective forces could not influence pathogenic traits. Abbreviations: BHI: brain-heart infusion agar; CRISPRs: Clustered regularly interspaced short palindromic repeats; Esp: Cell wall-associated protein; ENT: ear-nose-throat; ICU: intensive care units; OD: optical densities; PCR: polymerase chain reaction; SDS: sodium dodecyl sulfate; UTI: urinary tract infection